John Donne : the critical heritage - Smith, A. J. (Albert James), 1924-1991 (Critical heritage series., 1996)
The Critical Heritage gathers together a large body of critical sources on major figures in literature. Each volume presents contemporary responses to a writer's work, enabling students and researchers to read for themselves, for example, comments on early performances of Shakespeare's plays, or reactions to the first publication of Jane Austen's novels. The carefully selected sources range from landmark essays in the history of criticism to journalism and contemporary opinion, and little published documentary material such as letters and diaries. Significant pieces of criticism from later peri.